SUPPRESSION OF UPRISINGS IN THE SEMIRECHYE REGION BY THE TURKESTAN MILITARY DISTRICT AT THE BEGINNING OF THE 20th CENTURY (European Journal of Interdisciplinary Research and Development, 2026)
The article examines the protests, uprisings, and national liberation movements against the colonial regime in Turkestan in 1916, as well as the reasons for their emergence. The main object of research in the article is the uprising in the Semirechye region, which was one of the main centers of popular movements in Turkestan at the beginning of the 20th century. The origin of the uprising, the main armed resistance movements, and the difficulties in its suppression led the imperial administration in the region to rely on the troops of the Turkestan Military District. The brutal and chauvinistic attitude of the colonial armed forces toward the Turkestanis is revealed.